PENGARUH SUBSTITUSI PUPUK KIMIA DENGAN PUPUK ORGANIK TERHADAP SIFAT KIMIA DAN PRODUKTIVITAS JAGUNG DI ALFISOL JUMANTONO - Jauhari Syamsiyah; Ganjar Herdiyansyah; Sri Hartati; Suntoro Suntoro; Hery Widijanto; Intan Larasati; Nur Aisyah (Jurnal Tanah dan Sumberdaya Lahan, 2023)
Alfisols have low fertility, so fertilization is carried out to increase soil fertility and support the growth of maize plants. The continuous use of inorganic fertilizers in high quantities can cause land degradation, so it is necessary to reduce the amount by adding other fertilizers, such as organic fertilizers, as well as the relatively high price of inorganic fertilizers. This research was aimed to examine the potential of organic fertilizers in replacing inorganic fertilizers. The experimental design was a completely randomized block design with nine combination treatments of organic and inorganic fertilizers with three replications. The results showed fertilizer treatment ½ NPK + 1 PO affected and increased levels of organic C, CEC, base saturation, total N, and available P in Alfisols and maize yield. However, it did not significantly affect pH, base saturation and available S in Alfisols. The chemical properties of the soil had increased values ​​of 48%, 9.01%, 61.3%, and 134.5%, respectively. The treatment of ½ NPK + 1 PO  increased maize productivity by 47.76% compared to the control with the productivity of 12.7 t ha-1, which the results were not significantly different from standard NPK. Thus, the application of 10 t ha-1 of organic fertilizer has the potential to replace ½ doses of inorganic fertilizer.